2012
DOI: 10.4028/www.scientific.net/amr.554-556.1103
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activities and Phenolic Composition of Apple Peel, Core and Flesh Extracts on Selected Apple Cultivars

Abstract: Phenolic antioxidants have multiple benefits to human health. Polyphenols are responsible for the antioxidant activity in apples. Antioxidant activities were assessed using the ferric reducing/antioxidant power (FRAP) and 2,2-dipheny l-1-picrylhydrazyl (DPPH) radical scavenging assays in different cultivars and different parts of apples grown in China. The phenolic compounds and antioxidant activities differed significantly among the four apple cultivars. Guoguang had the highest phenolic concentration and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Apples are a significant part of the human diet, and they are ranked in the top five consumed fruits in the world . They have been identified as one of the main dietary sources of food antioxidants, mainly phenolic compounds such as flavonols, flavan-3-ols, phenolic acids, and dihydrochalcones, and they also possess high antioxidant capacity. These apple constituents are consistently associated with reduced risk of cancer, heart disease, asthma, and type II diabetes when compared to other fruits and vegetables and other sources of flavonoids. Apple consumption was also positively associated with increased lung function and weight loss. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Apples are a significant part of the human diet, and they are ranked in the top five consumed fruits in the world . They have been identified as one of the main dietary sources of food antioxidants, mainly phenolic compounds such as flavonols, flavan-3-ols, phenolic acids, and dihydrochalcones, and they also possess high antioxidant capacity. These apple constituents are consistently associated with reduced risk of cancer, heart disease, asthma, and type II diabetes when compared to other fruits and vegetables and other sources of flavonoids. Apple consumption was also positively associated with increased lung function and weight loss. ,, …”
Section: Introductionmentioning
confidence: 99%
“…As shown in this study, the peel had the ability to scavenge DPPH free radicals (IC 50 = 0.63 mg/mL), but in comparison, the core extract could not achieve 50% DPPH inhibition. In other studies, the IC 50 of Bali variety pineapple peel was reported as 1.13 mg/mL [45], and four different varieties of apple peel were reported as 3-6 mg/mL [12]. Thus, peel extract of the MD2 pineapple variety had a potent natural antioxidant ability.…”
Section: Tpc Tfc and Dpph Free Radical Scavenging Activitymentioning
confidence: 81%
“…Insoluble bound phenolics (IBP) are localized within the plant cell wall tissue structure and covalently bound to pectin, cellulose, hemicellulose, and structural proteins [11]. According to one study, apple peel contains more total phenolic (TPC) and flavonoid content (TFC) than apple core and flesh [12]. Montefusco et al [13] also highlighted that the total flavonoids in pomegranate peels were higher than in the fruit juice.…”
Section: Introductionmentioning
confidence: 99%
“…The differences in % D IA observed among ethanolic extract of AP fractions in this study can be associated with different distributions of polyphenolic compounds with different concentrations, their chemical composition, and the degree of possible oxidation [ 32 ]. The higher % D IA of the peel extract (fraction B) compared to other fractions could be due to the existence of a higher concentration of polyphenolic compounds including quercetin and quercetin glycosides, which are more potent in radical scavenging activity than some other polyphenols such as chlorogenic acid and phloridzin, which were detected in high concentration in seed and core extracts (fraction C) [ 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%